PENINGKATAN HASIL BELAJAR PESERTA DIDIK MENGGUNAKAN MODEL STEM PADA MATERI PENGUKURAN PANJANG DAN BERAT DI KELAS III SDN 19 SANTUR KOTA SAWAHLUNTO - Zahra Gustiani Putri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to improve students' learning outcomes on the material of length and weight measurement through the implementation of the STEM learning model in grade III at SDN 19 Santur, Sawahlunto City. The research problem formulation covers three aspects: (1) how to design a STEM-based teaching module that aligns with students' characteristics and measurement material; (2) how the learning process using the STEM model is conducted on length and weight measurement material; and (3) how students' learning outcomes improve after the implementation of the STEM model. This research uses the Classroom Action Research (CAR) method conducted in two cycles, each consisting of planning, implementation, observation,and reflection stages.The results of the study show that a contextually designed STEM-based teaching module provides opportunities for students to connect measurement concepts with real-life situations around them. The implementation of learning that integrates.